2018
DOI: 10.3920/bm2017.0193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined bifidobacteria supplementation and resistance training on cognitive function, body composition and bowel habits of healthy elderly subjects

Abstract: Physical exercise exerts favourable effects on brain health and quality of life of the elderly; some of these positive health effects are induced by the modulation of microbiota composition. We therefore conducted a randomised, double blind, placebo-controlled trial that assessed whether a combination of Bifidobacterium spp. supplementation and moderate resistance training improved the cognitive function and other health-related parameters in healthy elderly subjects. Over a 12-week period, 38 participants (66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 49 publications
0
77
0
4
Order By: Relevance
“…Anthropometric and blood pressure measurements were conducted at the beginning and at the end of the intervention period, as described previously. (18) To evaluate the body composition, a bioelectrical impedance analyzer (InBody S10, BioSpace, Seoul, Korea) was used.…”
Section: Methodsmentioning
confidence: 99%
“…Anthropometric and blood pressure measurements were conducted at the beginning and at the end of the intervention period, as described previously. (18) To evaluate the body composition, a bioelectrical impedance analyzer (InBody S10, BioSpace, Seoul, Korea) was used.…”
Section: Methodsmentioning
confidence: 99%
“…Results from preclinical and clinical studies suggest that probiotic administration may have positive effects in mental responses [ 117 , 118 ]. Few studies have investigated the effects of probiotic supplementation on the cognitive outcomes of athletes or physically active subjects [ 84 , 93 , 112 ] ( Table 2 ). In a group of highly trained, elite athletes, the self-rated sense of vigor (Profile of Mood States, POMS questionnaire) was significantly increased among the probiotic group, who ingested L. helveticus Lafti for 14 weeks, compared with the placebo group, with no difference in the total mood disturbance scores between groups detected [ 84 ].…”
Section: Probiotics As a Potential Ergogenic Aid To Enhance Physicmentioning
confidence: 99%
“…At the end of the intensive training period, significant differences in the scores related to sport recovery categories (the Recovery-Stress Questionnaire for Athletes) were detected between groups, showing that the scores of the probiotic group were more favorable compared with those in the placebo group. A training intervention performed in healthy, elderly, Japanese individuals demonstrated that a 12-week resistance training program induced beneficial effects on the general cognitive functions of both the placebo and probiotic groups [ 112 ]. The 12-week supplementation with multi-strain bifidobacteria significantly decreased overall mental state scores compared with baseline scores, with lower scores indicating lower depression and anxiety symptoms [ 112 ].…”
Section: Probiotics As a Potential Ergogenic Aid To Enhance Physicmentioning
confidence: 99%
“…Outro estudo observou que os grupos que receberam iogurte probiótico ou cápsulas probióticas tiveram queda da pontuação DASS de 10.3 e 9.5, respectivamente, comprovando atuação dos probióticos em ambas apresentações para os desfechos depressão, ansiedade e estresse [29]. Inoue et al [30] avaliaram indivíduos através do questionário MoCA-J e observaram que a ingestão de probióticos promoveu melhora da pontuação total nas questões de ansiedade e depressão e aumentou a função cognitiva dos indivíduos, apesar de também observarem melhora deste último aspecto no grupo controle, ainda que com escores menores. Steenberg et al [31], por sua vez, não observaram variação nas pontuações para depressão ou ansiedade entre grupo probiótico e placebo e salientam que sua população-alvo já começou o estudo com baixa pontuação, o que é esperado para indivíduos saudáveis.…”
Section: Evidências Da Ação Dos Probióticos No Tratamento Da Depressãounclassified
“…Apenas Romijn et al [34] investigaram o efeito da administração de probióticos a uma população com leve transtorno de humor e não observaram alteração nos desfechos estresse, depressão e ansiedade. Dois estudos avaliarem população idosa (acima de 65 anos), sendo que um deles suplementou apenas L. reuteri e não observou melhora nas condições dos participantes da pesquisa com o uso de probióticos [33], enquanto a outra pesquisa utilizou uma mistura de B. longum, B. infantis M-63 e B. breve, que promoveu melhora da saúde mental [30]. Tais achados mostram a importância de se avaliar o efeito de probióticos para populações específicas.…”
Section: Evidências Da Ação Dos Probióticos No Tratamento Da Depressãounclassified